VALUE-AND CHARACTER-BASED BASIC EDUCATION MANAGEMENT: A COMPARISON OF GLOBAL APPROACHES - Evi Gusliana; Agus Pahrudin; Yuberti Yuberti; Achi Rinaldi (El Midad, 2026)
This study aims to compare character education management policies and practices at the primary education level across ten countries (Indonesia, USA, Saudi Arabia, Australia, UK, Japan, Germany, Malaysia, Singapore, and China) through a Systematic Literature Review (SLR) method using the PRISMA protocol. Analysis of literature from 2015–2025 identifies three main clusters of approaches: (1) Eastern Values and Discipline-based approaches which are centralized and monolithic (Japan, China, Singapore); (2) Democratic Citizenship and Individual-based approaches emphasizing autonomy and curriculum integration (USA, UK, Australia, Germany); and (3) Religious and National Identity-based approaches (Saudi Arabia, Malaysia, Indonesia). The findings reveal significant variations in implementation strategies across subjects and curriculum integration, as well as in teacher roles, ranging from authoritative moral role models to ethical discussion facilitators. This study concludes that while no single model is universally effective, Indonesia can strengthen its system by adopting systematic habituation mechanisms from East Asia and critical reasoning development from the West to complement its strong religious value basis.